PENGHITUNGAN EMISI GAS RUMAH KACA (GRK) DARI SEKTOR SAMPAH PERKOTAAN DI INDONESIA - Purwanta, Wahyu (Jurnal Teknologi Lingkungan, 2009)
Indonesia produced 48.8 Mt/year of Municipal Solid Waste (MSW) with populationnumber of 218.8 million and rate of waste generation 0.61 kg/cap/day. Most ofMSW (40%) are transported to the Solid Waste Disposal Site (TPA) in urban area.The landfill site which is unmanaged will become a source of the GHGs emission,mainly the methane emission. Based on the Indonesian population, using FODIPCC Tier-2 method, CH4 generated from MSW sector (landfill only) in 2006 is109.96 Gg CH4 and will be increased up to 259 Gg in 2010, 504 Gg in 2015 and1,065 Gg in 2025. The increase number of this CH4 emission is caused by theincrease of population number that will increase the waste production and alsoincrease the volume waste that is collected in the disposal area. The future scenarioby referring to the national strategic plan which is developed by the Public WorkDepartment is that the waste should be reduced from the source, so the totalvolume will be reduced by 20% in 2010. In 2015, refers to the MDGs target, 80% ofthe MSW in urban area and 50% of the MSW in rural area should be transported tothe final disposal site. As stated in Solid Waste Management Act No 18/2008 andin accordance with the raw water protection, improvement of landfill quality fromopen dumping to sanitary landfill or controlled landfill and development of regionallandfill are the priority programs with national financial support as an initial investment.